Arthroscopic inspection after the surgical treatment of patella fractures - Haklar, Ugur (Springer-Verlag, 2008)
After the treatment of patella fractures the only way to evaluate healing at the articular surface before implant removal is through arthroscopy. The purpose of this study was to examine the healing potential of the cartilage. Arthroscopy was performed in 18 patients at the time of implant removal. The mean age of the patients was 42.1 years. The time elapsed from the index surgery to the arthroscopy and implant removal surgery was 12.9 months. During the arthroscopy, we inspected articular step-off, cartilage loss, and joint surface irregularities. Cartilage irregularities were observed in 13 of the 18 patients. Five patients had well-healed cartilage at the patellar surface. Although none of the patients had displacement at final follow-up X-rays, step-off was detected in two patients during arthroscopy. Our observation showed that cartilage lesions did not correlate with clinical and radiological evaluation. Despite good knee scores, we observed surface irregularities, chondral lesions, and fibrillation in most of the cases implicating subsequent patellofemoral arthritis.